Uncover The Construction of News about Plagiarism in Portal-Islam Media - Anjarsari, Riana; Nugraha Adiwijaya, Satria (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Submission of information from online to readers has various perceptions on the reader's cognition, especially in the aspect of work plagiarism. Unbalanced media coverage has diversified impacts. This also happened to the news that Afi Nihaya was accused of Plagiarism from Mita Handayani's account on the Islamic Portal online portal. In addition to the attention of news readers, the emergence of the news as a form of court that occurs in the community. This study aims to deconstruct the unfairness of online towards Afi Nihaya. The method used in this research is descriptive qualitative and using critical discourse analysis of Teun A. Van Dijk. Research data was taken from the Islamic portal about Afi Nihaya Accused of Plagiarism from Mita Handayani's account. The data analysis technique is based on the discourse analysis of Teun A. Van Dijk's model, namely text, social cognition, and social context. The results of this study (1) the text contains the discourse on the facts of plagiarism carried out by Afi Nihaya Faradisa; (2) social cognition/discourse practices that generate ideas and the alignments of journalists are both not in favor of Afi; (3) the social context/sociocultural practice which can be seen from the media's alignment in the resulting news is that they are both not in favor of Afi. Thus, online about Afi Nihaya Faradisa experiences injustice in the attitude and role of the news media, causing a shift in attitudes among readers